2001
DOI: 10.1084/jem.194.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Interleukin (Il)-18 Receptor α Chain Expression on Cd4+ T Cells during T Helper (Th)1/Th2 Differentiation

Abstract: Interleukin (IL)-18 has been well characterized as a costimulatory factor for the induction of IL-12–mediated interferon (IFN)-γ production by T helper (Th)1 cells, but also can induce IL-4 production and thus facilitate the differentiation of Th2 cells. To determine the mechanisms by which IL-18 might regulate these diametrically distinct immune responses, we have analyzed the role of cytokines in the regulation of IL-18 receptor α chain (IL-18Rα) expression. The majority of peripheral CD4+ T cells constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 36 publications
4
68
0
Order By: Relevance
“…It had been reported that IL-18R␣ is upregulated in established Th1 cells by TCR stimulation and IL-12, a STAT4 activator (19), which might question a role for T-bet in regulation of IL-18R␣ expression. However, TCR/IL-12-dependent upregulation of IL-18R␣ does not occur in Th1 cells prepared from IFN␥-deficient CD4 T cells and is restored by addition of exogenous IFN␥ (20). Because IFN␥ activates T-bet, these reports are consistent with a role for T-bet in Th1-cell IL-18R␣ induction.…”
Section: Upregulation Of Receptors For Il-1 Family Members and Mastersupporting
confidence: 78%
“…It had been reported that IL-18R␣ is upregulated in established Th1 cells by TCR stimulation and IL-12, a STAT4 activator (19), which might question a role for T-bet in regulation of IL-18R␣ expression. However, TCR/IL-12-dependent upregulation of IL-18R␣ does not occur in Th1 cells prepared from IFN␥-deficient CD4 T cells and is restored by addition of exogenous IFN␥ (20). Because IFN␥ activates T-bet, these reports are consistent with a role for T-bet in Th1-cell IL-18R␣ induction.…”
Section: Upregulation Of Receptors For Il-1 Family Members and Mastersupporting
confidence: 78%
“…1B). Although both Th1 and Th2 cells predominantly express the p38␣ isoform (our unpublished data), it is not surprising that there is no effect on Th2 cells since IL-4 negatively modulates the receptors for both IL-12 and IL-18 (10,11).…”
Section: Resultsmentioning
confidence: 99%
“…Although IL-18 alone does not appear to be sufficient for Th1 development (10 -11), T cells primed in the presence of IL-12 will subsequently respond to both IL-12 and IL-18 in a paracrine fashion by secreting large amounts of IFN-␥ (12)(13)(14). High levels of IL-18R␣ expression correlate with the ability of IL-18 to induce, as well as synergize with IL-12 for significant IFN-␥ production (7). This synergistic effect of IL-12 and IL-18 occurs in the absence of TCR ligation and may represent an alternative pathway for production of IFN-␥ during ongoing inflammatory responses.…”
Section: Role Of Ifn-␥ In Th1 Differentiation: Ifn-␥ Regulates Il-18rmentioning
confidence: 94%
“…Binding of IL-12 leads to IFN-␥ production and further enhancement of IL-12R␤2 expression (2)(3)(4)(5)(6). In addition to IL-12R␤2, IL-12 up-regulates IL-18R␣ expression (7)(8)(9). Although IL-18 alone does not appear to be sufficient for Th1 development (10 -11), T cells primed in the presence of IL-12 will subsequently respond to both IL-12 and IL-18 in a paracrine fashion by secreting large amounts of IFN-␥ (12)(13)(14).…”
Section: Role Of Ifn-␥ In Th1 Differentiation: Ifn-␥ Regulates Il-18rmentioning
confidence: 99%